EVALUATION OF IN VIVO IMMUNOMODULATORY ACTIVITY OF AQUEOUS AND ETHANOLIC EXTRACT OF CAPPARIS MOONII - G KANASE, VANITA; SHETTIGAR, SHRUTI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study was intended to evaluate the in vivo immunomodulatory activity of aqueous and ethanolic extract of dried fruits of Capparis moonii Wight. Methods: The effect of both the extracts was evaluated by carbon clearance assay in mice, and they showed a significant increase in the phagocytic index at 50, 100, and 200 mg/kg dose. The effect of the extracts on delayed-type hypersensitivity (DTH) and antibody titer assay was evaluated in ovalbumin immunized mice. Results: Both extracts showed a significant effect on DTH response and stimulation of antibody titer at 200 mg/kg dose. The effects of the extracts in cyclophosphamide-induced myelosuppression mice were also statistically significant. Conclusion: The studies demonstrated specific and non-specific immunostimulating properties of both the ethanol and aqueous extract of C. moonii fruits in various in vivo experimental methods suggesting its therapeutic usefulness in immunocompromised conditions.